High-resolution high-speed nanoindentation mapping of cement pastes: Unravelling the effect of microstructure on the mechanical properties of hydrated phases. (5th May 2016) - Sebastiani, M.; Moscatelli, R.; Ridi, F.; Baglioni, P.; Carassiti, F.
Abstract: Cementitious materials represent the most used materials in the construction industry. Their strong heterogeneity and multiscale microstructure make the study of the mechanical properties and the in-service behaviour very challenging: new techniques are required by industrial research to better investigate these aspects. In this work a novel technique based on statistical nanoindentation is exploited to obtain results about the microstructure build-up and the mechanical properties. An innovative high-speed nanoindentation method is here combined and compared with a standard nanoindentation procedure in order to get highly consistent statistical results. Combining the high-speed nanoindentation, the statistical deconvolution and SEM/EDS investigations, the main phases present in the tested hydrated cement paste have been characterized. High-resolution maps of the mechanical properties are in good agreement with SEM-EDS results. The evolution of the mechanical properties has been tested over the time and in particular after 1, 3, 5, 7, 14 and 28 days of hydration. It was found that the nano-mechanical properties were almost constant during the hydration time and the evolution of the bulk mechanical resistance properties of the cement paste is found to be due to a variation of the volume proportions between the three principal phases (low-density, high-density and ultra-high-density C–S–H). Graphical abstract: Highlights: High-speed nanoindentation gives unprecedented spatial resolution for nanomechanical mapping of heterogeneous materials, such as cement paste. Four distinct phases are identified for a cement paste by statistical deconvolution of high speed nanoindentation data. The elastic moduli of the four identified phases are independent of hydration time within the range 1–28 days. The conversion from Low-Density to High-Density (HD) and Ultra-HD calcium silicate hydrate (C-S-H) gives improved mechanical resistance.